1986
DOI: 10.1079/bjn19860105
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory nitrogen retention in growing pigs following a period of N deprivation

Abstract: 1. Semi-synthetic diets, with dried microbial cells (Pruteen) as the nitrogen source, were used to measure N retention in 50 kg pigs given different combinations of N intake involving periods of deprivation and enhanced 2. Metabolic faecal N losses were 1.92 g/d (1.26 g/kg dry matter eaten) and endogenous urinary losses were Many pigs undergo a period of growth during which deposition of protein proceeds at below the potential rate; for example, as a result of depressed feed intake following weaning or as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Previous studies have also reported that pigs subjected to dietary restrictions utilized feed more efficiently during the realimentation phase than unrestricted pigs . In other studies, the faster growth did not last throughout realimentation, but it was significantly exhibited throughout four to six weeks after the change in diet (Tulis & Whitemore, 1986;Skiba et al, 2001), while Therkildsen et al (2002) had proposed that at least 42 days of realimentation was required for full compensation.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have also reported that pigs subjected to dietary restrictions utilized feed more efficiently during the realimentation phase than unrestricted pigs . In other studies, the faster growth did not last throughout realimentation, but it was significantly exhibited throughout four to six weeks after the change in diet (Tulis & Whitemore, 1986;Skiba et al, 2001), while Therkildsen et al (2002) had proposed that at least 42 days of realimentation was required for full compensation.…”
Section: Discussionmentioning
confidence: 94%
“…In the cited literature, both ad libitum and restricted feeding were applied during realimentation, which proves that feeding regime and change in feeding behaviour are not the most important factors that influence the compensatory growth of animals. The faster growth rate does not last throughout realimentation, but it is significantly exhibited throughout 4-6 weeks after the change in diet (Tulis et al, 1986;Skiba et al, 2001). In most cases of compensatory growth, pigs characterize better the feed conversion ratio as compared with non-restricted animals.…”
Section: Growth Ratementioning
confidence: 85%
“…Compensatory N retention following the N deprivation in pigs has been demonstrated (Whittemore et al, 1978;Tullis et al, 1986), but a long-term effect of dietary restrictions on N balance in grower-finisher pigs has not been elucidated fully. The present study was conducted to investigate the effect of dietary amino acid restrictions during the grower phase on growth performance, serum metabolites, carcass and meat quality, and N balance in grower-finisher pigs.…”
mentioning
confidence: 99%